Organic chemistry - Carey, Francis A.
Written for the sophomore-level, two-semester organic course for majors in the science, pre-med, and chemical engineering, the second edition retains mechanisms within a functional group framework. The book employs summary tables, four-colour diagrams and illustrations, and end of chapter summaries to communicate important concepts. Coverage of reactions is selective, rather than encyclopedic. Rarely used reactions are not included, while the most commonly treated reactions are given thorough treatment. Carey's use of annotated summary tables has been expanded to include several types and more of each type. The tables include real examples from the chemical literature. 24 essays are now included, providing a combination of historical notes and additional insights into the contemporary relevance of organic chemistry